2015
DOI: 10.4314/afrrev.v9i4.1
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence and Sexual Health among Young Women in Zambia

Abstract: This paper aims at describing the prevalence and correlates of domestic violence, and evaluating their associations with key health outcomes among Zambian young females aged 15-24 years.Data from the 2007 Zambia Demographic Health Survey was utilized. The survey was carried out by Central Statistical Office with the technical assistance from Macro International through MEASURE DHS programme. The 2007 ZDHS is based on a nationally representative sample of 7146 ever married women of 15-49 age group covering 320 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…According to Lassi et al [6], due to the repeated state of neglect, abuse and fear, children in orphanages are one of the most vulnerable groups of children in society. Alcohol abuse has been also found to be common among young people in Zambia [7] and experience of sexual violence in young women [8].Further, Lassi et al [6], observed in a study on Eritrean orphanages that, children were found with mood disturbances, language delays and disturbed social interaction with peers. It was concluded that orphanages are necessarily the breeding grounds of psychopathological problems .Peer relational competence is a phrase that was used to refer to the adolescent's ability to amicably and confidently interact with peers in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…According to Lassi et al [6], due to the repeated state of neglect, abuse and fear, children in orphanages are one of the most vulnerable groups of children in society. Alcohol abuse has been also found to be common among young people in Zambia [7] and experience of sexual violence in young women [8].Further, Lassi et al [6], observed in a study on Eritrean orphanages that, children were found with mood disturbances, language delays and disturbed social interaction with peers. It was concluded that orphanages are necessarily the breeding grounds of psychopathological problems .Peer relational competence is a phrase that was used to refer to the adolescent's ability to amicably and confidently interact with peers in the environment.…”
Section: Introductionmentioning
confidence: 99%